Transparent environment-friendly calcium-zinc heat stabilizer as well as preparation method and application thereof

By modifying hydrotalcite and epoxy soybean oil, combined with calcium and zinc salts, a transparent and environmentally friendly calcium and zinc heat stabilizer is prepared, which solves the problems of environmental pollution and high cost in the prior art, and achieves high thermal stability and transparency of PVC.

CN119591935APending Publication Date: 2025-03-11台州联成新材料有限公司

Patent Information

Application Number
CN202411711644.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, thermal stabilizers used for PVC have environmental pollution problems and are costly, making it difficult to meet environmentally friendly needs.

Method used

A transparent and environmentally friendly calcium and zinc heat stabilizer is prepared by modifying hydrotalcite and epoxy soybean oil, combined with calcium and zinc salts as main stabilizers. Modified hydrotalcite reacts with the hydroxyl group on the surface of the hydrotalcite through a silane coupling agent to reduce hydrogen bonding and improve dispersion and thermal stability; modified epoxy soybean oil increases epoxy groups and ether bonds through ring opening, chlorination and grafting reactions, and improves compatibility and thermal stability with PVC.

Benefits of technology

It achieves high thermal stability and transparency of PVC, while being environmentally friendly and at the same time, it is low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005155893760000081
    Figure BDA0005155893760000081
Patent Text Reader

Abstract

The invention relates to the technical field of chemical stabilizers, in particular to a transparent environment-friendly calcium-zinc heat stabilizer and a preparation method thereof.The transparent environment-friendly calcium-zinc heat stabilizer is prepared from, by weight, 10-25 parts of calcium salt, 10-25 parts of zinc salt, 6-8 parts of modified hydrotalcite, 4-6 parts of lubricant, 2-4 parts of antioxidant, 2-4 parts of ultraviolet light absorber and 2-4 parts of modified epoxidized soybean oil. The transparent environment-friendly calcium-zinc heat stabilizer prepared by the method has excellent heat resistance and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical stabilizers, and specifically relates to a transparent and environmentally friendly calcium zinc heat stabilizer and a preparation method and application thereof. Background Art

[0002] PVC is a polymer compound formed by the polymerization of polyvinyl chloride monomers. It is one of the most in-demand plastics in the world. PVC material has good corrosion resistance to inorganic acids and alkalis, and has good mechanical strength and insulation. It also has good processability and can be processed by extrusion, injection molding, blow molding and other methods. It is widely used in engineering construction, packaging materials, medical equipment, electrical and other fields. However, since the chain segments of PVC contain double bonds, branching points and initiator residues, during the processing, chlorine atoms are easily released from the molecular chain to form hydrogen chloride, which accelerates the degradation of PVC, shortens the life of PVC products, and deepens the color. Therefore, heat stabilizers used for PVC have been extensively studied by researchers in this field.

[0003] Patent CN105385072B discloses a PVC calcium zinc heat stabilizer, including the following components: zinc stearate or calcium stearate or a mixture of the two, an auxiliary heat stabilizer, an internal lubricant, an external lubricant, an antioxidant, an ultraviolet absorber, and a dispersant. By optimizing the types and amounts of calcium zinc soap, antioxidant, and ultraviolet absorber, a heterocyclic epoxy compound is added as an auxiliary heat stabilizer, which not only solves the transparency requirements of the PVC film, but also meets the requirements of long-term thermal stability. The auxiliary heat stabilizer used in the invention contains triglycidyl isocyanurate, which is harmful to the environment and is not environmentally friendly.

[0004] Patent CN115232363B discloses a composite calcium-zinc heat stabilizer composition, a preparation method and an application thereof, comprising the following raw materials: a calcium-zinc heat stabilizer, modified fumed silica, and terminal hydroxylated pentaerythritol adipate; the invention uses modified fumed silica, terminal hydroxylated pentaerythritol adipate and a calcium-zinc heat stabilizer in combination and synergistically enhances the effect, so that the composite calcium-zinc heat stabilizer composition has excellent thermal stability, but the price of fumed silica is relatively high.

[0005] Therefore, there is an urgent need in the market for an environmentally friendly, low-cost, transparent, environmentally friendly calcium-zinc heat stabilizer. Summary of the invention

[0006] In order to overcome the above-mentioned deficiencies of the prior art, the present invention provides a transparent and environmentally friendly calcium zinc heat stabilizer, which is environmentally friendly.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a transparent and environmentally friendly calcium zinc heat stabilizer, which comprises the following raw materials, by weight: 10-25 parts of calcium salt, 10-25 parts of zinc salt, 6-8 parts of modified hydrotalcite, 4-6 parts of lubricant, 2-4 parts of antioxidant, 2-4 parts of ultraviolet absorber, and 2-4 parts of modified epoxidized soybean oil.

[0009] In some embodiments, the preparation method of the modified hydrotalcite comprises the following steps: adding hydrotalcite and γ-methacryloxypropyltrimethoxysilane to ethanol, stirring at 50-60°C for 5-6 hours, then adding 1-vinylimidazole and azobisisobutyronitrile and stirring at 70-80°C for 1-2 hours, filtering, washing, and drying to obtain the modified hydrotalcite.

[0010] Hydrotalcite contains a large amount of hydroxyl groups which can absorb hydrogen chloride generated by PVC and reduce the catalytic effect of hydrogen chloride on the degradation of PVC. However, due to the presence of a large amount of hydroxyl groups on the surface of hydrotalcite, they are easily attracted to each other through hydrogen bonding, causing agglomeration, uneven dispersion in PVC, and easy precipitation during long-term heat processing. The present invention modifies the hydrotalcite, and the modified hydrotalcite has good dispersibility in PVC and increases the toughness and thermal stability of PVC. The possible reason is that the silane coupling agent reacts with the hydroxyl groups on the surface of the hydrotalcite, reducing the hydrogen bonding effect and reducing the agglomeration phenomenon. At the same time, a certain amount of alkane chain segments exists, which increases the toughness of PVC to a certain extent. In addition, the imidazole group has greater activity and can react with hydrogen chloride, which is beneficial to stabilizing the unstable chlorine atoms in PVC, and further improving the thermal stability of PVC.

[0011] In some embodiments, the mass ratio of the hydrotalcite, γ-methacryloxypropyltrimethoxysilane and 1-vinylimidazole is 1:(0.5-0.6):(0.2-0.3).

[0012] The present invention limits the mass ratio of hydrotalcite, gamma-methacryloxypropyltrimethoxysilane and 1-vinylimidazole so that part of the hydroxyl groups on the surface of the hydrotalcite react with the 1-vinylimidazole, weakens the hydrogen bonding effect, and enables the hydrotalcite to be evenly dispersed. Meanwhile, the presence of the imidazole group avoids the problem that the thermal stability of PVC decreases due to the reduction of the amount of hydroxyl groups in the hydrotalcite.

[0013] In some embodiments, the lubricant is one or more of polyethylene wax, paraffin wax, stearic acid amide, and Fischer-Tropsch wax.

[0014] Preferably, the lubricant is stearic acid amide.

[0015] In some embodiments, the ultraviolet absorber is 2-hydroxy-4-(methacryloyloxy)benzophenone or 2-hydroxy-4-propyleneoxybenzophenone.

[0016] In some embodiments, the method for preparing the modified epoxidized soybean oil comprises the following steps:

[0017] (1) adding epoxidized soybean oil to triethylamine, stirring at 65-75° C. for 1-2 hours, cooling, and then adding thionyl chloride at 0-5° C. while stirring for 3-5 hours to obtain chloroepoxidized soybean oil;

[0018] (2) adding the chlorinated epoxidized soybean oil, pentaerythritol triacrylate, hydroquinone and 4-dimethylaminopyridine obtained in step (1) into dichloromethane, stirring at 25-35° C. for 35-37 hours, and distilling to obtain multi-double bond epoxidized soybean oil;

[0019] (3) Add the multi-double-bond epoxy soybean oil obtained in step (2) to formic acid, then add concentrated sulfuric acid and heat to 45-55° C., add 28-32wt% hydrogen peroxide, stir for 20-30 min, add 28-32wt% hydrogen peroxide again, stir and react for 7.5-8.5 h, extract, wash and distill to obtain modified epoxy soybean oil.

[0020] Epoxy groups can capture free radicals generated by PVC degradation, quickly absorb hydrogen chloride, prevent PVC from releasing hydrogen chloride, and terminate degradation. Under the synergistic effect of metal salts, thermal stability can be effectively improved. However, the compatibility of epoxy soybean oil with PVC is relatively poor. The present invention opens the ring of epoxy soybean oil and then adds chlorine atoms, then reacts with the hydroxyl group of pentaerythritol triacrylate to graft multiple double bonds, and then epoxidizes to form multiple epoxy groups. The modified epoxy soybean oil has good compatibility in PVC and increased thermal stability. The possible reason is that the modified epoxy soybean oil has increased ether bonds and acrylate groups, which are similar to the polarity of PVC, so that the compatibility between the two is increased. On the other hand, the number of epoxy groups is increased, the ability to absorb hydrogen chloride is increased, and the thermal stability is further increased.

[0021] In some embodiments, the mass ratio of the epoxy soybean oil to thionyl chloride is 1:(0.6-0.8).

[0022] In some embodiments, the mass ratio of chloroepoxidized soybean oil to pentaerythritol triacrylate in step (2) is 1:(4-5).

[0023] The invention limits the mass ratio of epoxy soybean oil to thionyl chloride to ensure that sufficient chlorine atoms in the system react with hydroxyl groups of the ring-opened epoxy soybean oil to obtain chlorinated epoxy soybean oil, and then limits the mass ratio of chlorinated epoxy soybean oil to pentaerythritol triacrylate to provide sufficient hydroxyl groups to react with chlorinated epoxy soybean oil, graft multiple double bonds, and simultaneously form multiple ether bonds to increase the compatibility with PVC.

[0024] The second aspect of the present invention provides a method for preparing a transparent environmentally friendly calcium zinc heat stabilizer, comprising the following steps:

[0025] S1. Add calcium salt, zinc salt, modified hydrotalcite, lubricant, antioxidant and ultraviolet absorber into a mixer and stir at room temperature for 40-60 minutes to obtain a premix;

[0026] S2. Add the premix obtained in step S1 into the modified epoxy soybean oil and stir for 30-40 minutes at a rotation speed of 300-400 rpm to obtain a transparent and environmentally friendly calcium zinc heat stabilizer.

[0027] The third aspect of the present invention provides an application of a transparent and environmentally friendly calcium zinc heat stabilizer, wherein the transparent and environmentally friendly calcium zinc heat stabilizer is used for preparing PVC, and the addition amount is 2-4wt%.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention obtains a calcium zinc heat stabilizer by modifying hydrotalcite and epoxidized soybean oil and using calcium salt and zinc salt as main stabilizers in combination with other additives. The calcium zinc heat stabilizer has good thermal stability, high transparency and is relatively environmentally friendly.

[0030] 2. The present invention reduces hydrogen bonding and agglomeration by reacting the silane coupling agent with the hydroxyl groups on the surface of the hydrotalcite. At the same time, a certain amount of alkane segments are present, which increases the toughness of the PVC to a certain extent. In addition, the imidazole group has greater activity and can react with hydrogen chloride, which is beneficial to stabilizing the unstable chlorine atoms in the PVC, further improving the thermal stability of the PVC.

[0031] 3. The present invention adds chlorine atoms after ring opening of epoxy soybean oil, and then reacts with the hydroxyl group of pentaerythritol triacrylate to graft multiple double bonds, and then epoxidizes to form multiple epoxy groups. The modified epoxy soybean oil adds ether bonds and acrylate groups in PVC and has good compatibility with PVC. In addition, the number of epoxy groups is increased, the ability to absorb hydrogen chloride is increased, and the thermal stability is further increased. DETAILED DESCRIPTION

[0032] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following examples and comparative examples are only used to illustrate the present invention and are not intended to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0033] In order to facilitate those skilled in the art to implement the present invention, some raw materials and manufacturers of the embodiments and comparative examples are described as follows:

[0034] The compounds and related reagents used in the following examples and comparative examples can all be purchased from the market, among which PVC was purchased from Dongguan Jingke Polymer Co., Ltd.; hydrotalcite was purchased from Kaisima (Dandong) High-tech Materials Technology Co., Ltd., model ALCAMIZER 1-C; epoxidized soybean oil was purchased from Shandong Xinqi Chemical Co., Ltd., with a weight average molecular weight of 1000.

[0035] Preparation Example 1

[0036] The preparation method of modified hydrotalcite-1 comprises the following steps: adding 10 g of hydrotalcite and 5.5 g of γ-methacryloxypropyltrimethoxysilane to 50 ml of anhydrous ethanol, stirring at 55° C. for 5.5 h, then adding 2.5 g of 1-vinylimidazole and 0.1 g of azobisisobutyronitrile, stirring at 75° C. for 1.5 h, washing, and drying to obtain modified hydrotalcite-1.

[0037] Preparation Example 2

[0038] The preparation method of modified hydrotalcite-2 has the same specific steps as Preparation Example 1, except that the added amount of γ-methacryloxypropyltrimethoxysilane is 7.5 g.

[0039] Preparation Example 3

[0040] The preparation method of modified hydrotalcite-3 has the same specific steps as Preparation Example 1, except that the added amount of 1-vinylimidazole is 4 g.

[0041] Preparation Example 4

[0042] The preparation method of modified epoxidized soybean oil-1 comprises the following steps:

[0043] (1) 10 g of epoxidized soybean oil was added to 1 g of triethylamine, stirred at 70° C. for 1.5 h, cooled, and then 7 g of dichlorothionyl was added at 2° C. while stirring for 3.5 h to obtain chloroepoxidized soybean oil;

[0044] (2) adding 10 g of the chloroepoxidized soybean oil obtained in step (1), 4.5 g of pentaerythritol triacrylate, 1 g of hydroquinone and 0.5 g of 4-dimethylaminopyridine to 100 ml of dichloromethane, stirring at 30° C. for 36 h, and distilling to obtain multi-double bond epoxidized soybean oil;

[0045] (3) 10 g of the multi-double-bond epoxy soybean oil obtained in step (2) was added to 10 g of formic acid, followed by 0.05 g of 98 wt % concentrated sulfuric acid, the temperature was raised to 50° C., 1 g of 30 wt % hydrogen peroxide was added, and the mixture was stirred for 25 min. 5 g of 30 wt % hydrogen peroxide was added again and stirred for 8 h. The mixture was extracted, washed, and distilled to obtain modified epoxy soybean oil-1.

[0046] Preparation Example 5

[0047] The preparation method of modified epoxy soybean oil-2 has the same specific steps as Preparation Example 4, except that the amount of thionyl chloride added is 4 g.

[0048] Preparation Example 6

[0049] The preparation method of modified epoxidized soybean oil-3 has the same specific steps as Preparation Example 4, except that the added amount of pentaerythritol triacrylate is 7 g.

[0050] Example 1

[0051] A transparent and environmentally friendly calcium zinc heat stabilizer comprises the following raw materials, measured in parts by weight: 18 parts of calcium stearate, 18 parts of zinc stearate, 7 parts of modified hydrotalcite-1, 5 parts of stearic acid amide, 3 parts of antioxidant 1010, 3 parts of 2-hydroxy-4-(isobutyleneoxy)benzophenone, and 3 parts of modified epoxy soybean oil-1.

[0052] The preparation method of the transparent environmentally friendly calcium zinc heat stabilizer in this embodiment comprises the following steps:

[0053] S1, adding calcium stearate, zinc stearate, modified hydrotalcite-1, stearic acid amide, antioxidant 1010, and 2-hydroxy-4-(isobutylene acyloxy) benzophenone into a mixer, and stirring at room temperature for 50 minutes to obtain a premix;

[0054] S2. The premix obtained in step S1 was added to the modified epoxy soybean oil-1 in three equal portions and stirred for 35 minutes at a rotation speed of 350 rpm to obtain a transparent and environmentally friendly calcium zinc heat stabilizer.

[0055] Example 2

[0056] A transparent and environmentally friendly calcium zinc heat stabilizer comprises the following raw materials, measured in parts by weight: 10 parts of calcium stearate, 10 parts of zinc stearate, 6 parts of modified hydrotalcite-1, 4 parts of stearic acid amide, 2 parts of antioxidant 1010, 2 parts of 2-hydroxy-4-(isobutyleneoxy)benzophenone, and 2 parts of modified epoxy soybean oil-1.

[0057] The preparation method of the transparent environmentally friendly calcium zinc heat stabilizer in this embodiment comprises the following steps:

[0058] S1, adding calcium stearate, zinc stearate, modified hydrotalcite-1, stearic acid amide, antioxidant 1010, and 2-hydroxy-4-(isobutylene acyloxy) benzophenone into a mixer, and stirring at room temperature for 40 minutes to obtain a premix;

[0059] S2. Add the premix obtained in step S1 into the modified epoxy soybean oil-1 in three equal portions and stir for 30 minutes at a rotation speed of 400 rpm to obtain a transparent and environmentally friendly calcium zinc heat stabilizer.

[0060] Example 3

[0061] A transparent and environmentally friendly calcium zinc heat stabilizer comprises the following raw materials, measured in parts by weight: 25 parts of calcium stearate, 25 parts of zinc stearate, 8 parts of modified hydrotalcite-1, 6 parts of stearic acid amide, 4 parts of antioxidant 1010, 4 parts of 2-hydroxy-4-(isobutyleneoxy)benzophenone, and 4 parts of modified epoxy soybean oil-1.

[0062] The preparation method of the transparent environmentally friendly calcium zinc heat stabilizer in this embodiment comprises the following steps:

[0063] S1, adding calcium stearate, zinc stearate, modified hydrotalcite-1, stearic acid amide, antioxidant 1010, and 2-hydroxy-4-(isobutylene acyloxy) benzophenone into a mixer, and stirring at room temperature for 60 minutes to obtain a premix;

[0064] S2. Add the premix obtained in step S1 into the modified epoxy soybean oil-1 in three equal portions and stir for 40 minutes at a rotation speed of 300 rpm to obtain a transparent and environmentally friendly calcium zinc heat stabilizer.

[0065] Example 4

[0066] A transparent and environmentally friendly calcium zinc heat stabilizer and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified hydrotalcite-1 is replaced by modified hydrotalcite-2.

[0067] Example 5

[0068] A transparent and environmentally friendly calcium zinc heat stabilizer and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified hydrotalcite-1 is replaced by modified hydrotalcite-3.

[0069] Example 6

[0070] A transparent and environmentally friendly calcium zinc heat stabilizer and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified epoxidized soybean oil-1 is replaced by modified epoxidized soybean oil-2.

[0071] Example 7

[0072] A transparent and environmentally friendly calcium zinc heat stabilizer and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified epoxidized soybean oil-1 is replaced by modified epoxidized soybean oil-3.

[0073] Comparative Example 1

[0074] A transparent and environmentally friendly calcium zinc heat stabilizer and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified hydrotalcite-1 is replaced by hydrotalcite.

[0075] Comparative Example 2

[0076] A transparent and environmentally friendly calcium zinc heat stabilizer and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified epoxidized soybean oil-1 is replaced by epoxidized soybean oil.

[0077] Performance Test:

[0078] 1. Thermal stability test

[0079] 3 parts by weight of the transparent and environmentally friendly calcium zinc heat stabilizer prepared in each embodiment and comparative example was added to 100 parts by weight of PVC, mixed in a high-speed mixer for 10 minutes, discharged, and smelted into sheets on a double-roller mill. The sheets were molded into 4 mm sheets using a hot molding machine as samples, and the yellowness index of the samples was tested according to HG / T 3862-2006.

[0080] 2. Precipitation test

[0081] Take 3 parts by weight of the transparent and environmentally friendly calcium zinc heat stabilizer prepared in the above embodiments and comparative examples and 100 parts by weight of PVC and add them into the extruder for extrusion experiment. The extrusion temperature is 170°C. After continuously starting the machine for 4 hours, observe whether there is precipitate at the die, and weigh the mass of the precipitate. <1mg is Grade I, 1-5mg is Grade II, and >5mg is Grade III.

[0082] The test results are shown in Table 1

[0083] Table 1

[0084]

[0085] By comparing the data of Examples 1-3 in Table 1, it can be seen that the PVC prepared by the transparent environmentally friendly calcium zinc heat stabilizer of the present invention has a lower yellow index and good thermal stability; by comparing Examples 4 and 5 with Example 1, it can be seen that the change in the ratio of hydrotalcite, γ-methacryloxypropyltrimethoxysilane and 1-vinylimidazole may lead to a decrease in the adsorption capacity of hydrotalcite for hydrogen chloride, an increase in the yellow index of PVC, and a decrease in thermal stability; by comparing Examples 6 and 7 with Example 1, it can be seen that the change in the ratio of epoxy soybean oil to dichloride and the ratio of chloroepoxidized soybean oil to pentaerythritol triacrylate leads to a decrease in compatibility with PVC, an increase in the yellow index of PVC, and a decrease in thermal stability; by comparing Comparative Example 1 with Example 1, it can be seen that the direct use of hydrotalcite has poor dispersibility, PVC has a large yellow index, and poor thermal stability; by comparing Comparative Example 2 with Example 1, it can be seen that the direct use of epoxy soybean oil has poor compatibility with PVC, and all properties of PVC are reduced.

[0086] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A transparent and environmentally friendly calcium zinc heat stabilizer, characterized in that: The invention comprises the following raw materials in parts by weight: 10-25 parts of calcium salt, 10-25 parts of zinc salt, 6-8 parts of modified hydrotalcite, 4-6 parts of lubricant, 2-4 parts of antioxidant, 2-4 parts of ultraviolet absorber and 2-4 parts of modified epoxidized soybean oil.

2. The transparent and environmentally friendly calcium zinc heat stabilizer according to claim 1, characterized in that: The preparation method of the modified hydrotalcite comprises the following steps: adding hydrotalcite and γ-methacryloxypropyltrimethoxysilane into ethanol, stirring at 50-60° C. for 5-6 hours, then adding 1-vinylimidazole and azobisisobutyronitrile, stirring at 70-80° C. for 1-2 hours, filtering, washing and drying to obtain the modified hydrotalcite.

3. The transparent and environmentally friendly calcium zinc heat stabilizer according to claim 2, characterized in that: The mass ratio of the hydrotalcite, γ-methacryloxypropyltrimethoxysilane and 1-vinylimidazole is 1:(0.5-0.6):(0.2-0.3).

4. The transparent and environmentally friendly calcium zinc heat stabilizer according to claim 1, characterized in that: The lubricant is one or more of polyethylene wax, paraffin wax, stearic acid amide, and Fischer-Tropsch wax.

5. The transparent and environmentally friendly calcium zinc heat stabilizer according to claim 1, characterized in that: The ultraviolet absorber is 2-hydroxy-4-(isobutyleneoxy)benzophenone or 2-hydroxy-4-propyleneoxybenzophenone.

6. The transparent and environmentally friendly calcium zinc heat stabilizer according to claim 1, characterized in that: The preparation method of the modified epoxidized soybean oil comprises the following steps: (1) Add epoxidized soybean oil to triethylamine, stir at 65-75°C for 1-2 hours, cool, then add thionyl chloride at 0-5°C while stirring for 3-5 hours to obtain chloroepoxidized soybean oil; (2) adding the chlorinated epoxidized soybean oil, pentaerythritol triacrylate, hydroquinone and 4-dimethylaminopyridine obtained in step (1) into dichloromethane, stirring at 25-35° C. for 35-37 hours, and distilling to obtain multi-double bond epoxidized soybean oil; (3) Add the multi-double-bond epoxy soybean oil obtained in step (2) to formic acid, then add concentrated sulfuric acid and heat to 45-55° C., add 28-32wt% hydrogen peroxide, stir for 20-30 min, add 28-32wt% hydrogen peroxide again, stir and react for 7.5-8.5 h, extract, wash and distill to obtain modified epoxy soybean oil.

7. The transparent and environmentally friendly calcium zinc heat stabilizer according to claim 6, characterized in that: The mass ratio of the epoxy soybean oil to thionyl chloride is 1:(0.6-0.8).

8. The transparent and environmentally friendly calcium zinc heat stabilizer according to claim 6, characterized in that: In the step (2), the mass ratio of chloroepoxidized soybean oil to pentaerythritol triacrylate is 1:(4-5).

9. A method for preparing a transparent and environmentally friendly calcium zinc heat stabilizer according to any one of claims 1 to 8, characterized in that: The following steps are included S1. Add calcium salt, zinc salt, modified hydrotalcite, lubricant, antioxidant and ultraviolet absorber into a mixer and stir at room temperature for 40-60 minutes to obtain a premix; S2. Add the premix obtained in step S1 to the modified epoxy soybean oil and stir for 30-40 minutes at a rotation speed of 300-400 rpm to obtain a transparent and environmentally friendly calcium zinc heat stabilizer.

10. Use of the transparent and environmentally friendly calcium zinc heat stabilizer according to any one of claims 1 to 8 or the transparent and environmentally friendly calcium zinc heat stabilizer obtained by the preparation method according to claim 9, characterized in that: The transparent environmentally friendly calcium zinc heat stabilizer is used to prepare PVC, and the addition amount is 2-4wt%.

Citation Information

Patent Citations

  • PVC calcium zinc heat stabilizer and its auxiliary heat stabilizer

    CN105385072B

Cited By

  • PVC (polyvinyl chloride) fireproof plate prepared from oyster shells and preparation method of PVC fireproof plate

    CN120988407A